2022
DOI: 10.1002/ajmg.a.62851
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear nerve deficiency in SOX11‐related Coffin‐Siris syndrome

Abstract: The phenotypic spectrum of SOX11-related Coffin-Siris syndrome (CSS) is expanding with reports of new associations. SOX11 is implicated in neurogenesis and inner ear development. Cochlear nerve deficiency, absence or hypoplasia, is commonly associated with cochlear canal stenosis or with CHARGE syndrome, a monogenic condition that affects inner ear development. SOX11 is a transcription factor essential for neuronal identity, highly correlated with the expression of CHD7, which regulates SOX11. We present two u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Literature deals with a total of 82 subjects with pathogenic variants in SOX11 , including complete gene deletions (14%), missense (74%) and loss‐of‐function (12%) variants 4,5,7–19 . Detailed clinical information and clinical pictures were available for 32/82 subjects, including our patient.…”
Section: Resultsmentioning
confidence: 99%
“…Literature deals with a total of 82 subjects with pathogenic variants in SOX11 , including complete gene deletions (14%), missense (74%) and loss‐of‐function (12%) variants 4,5,7–19 . Detailed clinical information and clinical pictures were available for 32/82 subjects, including our patient.…”
Section: Resultsmentioning
confidence: 99%
“…(2) Compared with prior CSS-9-related publications including nonsystematic literature review (Alburaiky et al, 2022;Al-Jawahiri et al, 2022;Diel et al, 2021;Ding et al, 2022;Hanker et al, 2022;Khan et al, 2018;Okamoto et al, 2018;Wakim et al, 2021), we did a systematic literature review in this study on reported CSS-9 cases and found that pathogenic SOX11 SNVs altering the HMG domain were more likely to cause the widest range of organ anomalies, reminding patients carrying those variants should be aware of potential risks of having multiple organ anomalies and need thorough clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Among these CSS subtypes, CSS‐9 (OMIM#615866) is caused by heterozygous deficiency in the SRY‐related HMG‐box 11 ( SOX11 ) gene on 2p25.2, which is an expression regulation gene that encoded an important functional domain, high‐mobility group (HMG) box, and involved in the process of chromatin remodeling (Tsurusaki et al, 2014). CSS‐9 patients have been found to have cleft palate, hearing loss (including conductive and sensorineural subtypes), inner ear malformation (such as cochlear hypoplasia), ophthalmic, and genitourinary abnormalities in recent years (Alburaiky et al, 2022; Diel et al, 2021; Khan et al, 2018; Neirijnck et al, 2018; Wang et al, 2023), and the phenotypic spectrum of CSS‐9 has been expanded further (Al‐Jawahiri et al, 2022), but no studies thus far have documented the external ear malformation caused by SOX11 deficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Nevertheless, there may still be genetic determinants that underlie these 2 origins. For example, CND has been reported in patients with CHARGE, VACTERL, and Coffin-Siris syndromes, [51][52][53] which are hereditary and associated with USNHL. 54 Furthermore, multiple genes have been documented involved in inner ear malformations in syndromic and nonsyndromic SNHL.…”
Section: Discussionmentioning
confidence: 99%